TINJAUAN HUKUM EKONOMI SYARI’AH TERHADAP PRAKTEK BAGI HASIL TERNAK SAPI (Studi Kasus Di Desa Sidoharjo Kecamatan Jati Agung Kabupaten Lampung Selatan) - Gusri Isbaldi; Lisa Efrina; Estelee Elora Akbar (Sharing: Journal of Islamic Economics Management and Business, 2023)
The point of this exploration is to figure out how mudharabah contracts are executed in Sidoharjo Town and to figure out the perspective on sharia monetary regulation in regards to the framework utilized. In this examination, the strategy utilized is field research with a subjective graphic methodology and the information assortment techniques utilized are organized perception, meetings and documentation. The sources in this examination were individuals who keep cows and cow proprietors in Sidoharjo Town. The examination results show that assuming that there is a benefit sharing framework in bringing cows up in Sidoharjo Town, Jati Agung Locale, South Lampung Rule, there are two benefit sharing frameworks, the first is by separating the calves that have been conceived. cows that have been cared for by their managers. Second, by isolating the benefits from the offer of steers that have been raised by the rancher subsequent to returning the capital. This collaboration is clear in deciding beginning capital and steers costs. Concerning the survey of Sharia Monetary Regulation in view of the Accumulation of Sharia Financial Regulation, the execution of the benefit sharing framework in bringing dairy cattle up in Sidoharjo Town, Jati Agung Locale, South Lampung Rule as far as benefit imparting is in agreement to appropriate guidelines. type of thought. Be that as it may, assuming a misfortune happens, this cooperation doesn't contain a component of dharar (risk) since it is commonly useful when it comes time to share the benefits and both will encounter more noteworthy misfortunes in the event that the cow they are raising kicks the bucket. Consequently, the benefit sharing collaboration did by the local area in Sidoharjo Town is as per what has been managed in the Sharia Financial Regulation Accumulation.